ADSORPTION OF MERCURY (II) FROM AQUEOUS SOLUTION BY CRUMB RUBBER SLUDGE: ISOTHERM AND KINETIC STUDIES - Kasman, Monik; Hadrah Hasan; Titania Eno Widyaningsih (Yayasan Nuraini Ibrahim Mandiri, 2025)
The use of two different crumb rubber adsorbent (CRS), pure crumb rubber sludge (pCRS) and modified crumb rubber sludge (mPCRS) with HNO3 activator was investigated for the removal of Hg(II) from aqueous solution. Batch experiment was conducted to analyze the effect of adsorbent dosage and contact time on the adsorption capacities of pCRS and mCRS. Adsorption isotherm and adsorption kinetics was also analyzed to get description of the adsorption mechanism and the adsorbent properties. The Langmuir isotherm provided the best correlation with the maximum adsorption capacity was 16.00 mg/g an, 17.513 mg/g for respected to pCRS and mCRS. The kinetics studies showed that the Hg(II) for both adsorbents adsorbed rapidly which can be adjusted to the pseudo second order model. Our current study confirmed that CRS was effective adsorbent for the removal of Hg(II) from aqueous solution which followed monolayer and multilayer chemisorption